Coupling coordination evaluation and driving factor analysis of economic performance and social equity in rail transit station areas - Tianyue Wan; Wei Lu; Liang Wu; Wenzhi Rong (Frontiers of Architectural Research)
Transit-oriented development (TOD) is increasingly recognized as a key strategy for enhancing transportation efficiency, environmental sustainability, and economic vitality while fostering inclusive communities in dense, multifunctional urban areas. However, the relationship between TOD's economic benefits and social equity remains underexplored. This study critically evaluates TOD in Dalian, China, introducing the expanded Node-Place-Economy (NPE) model, which integrates economic and social dimensions into the traditional Node-Place model. The NPE model offers a comprehensive framework for assessing TOD effectiveness, particularly in balancing economic growth and equitable resource distribution. The research highlights significant disparities between central and peripheral regions, with central areas performing better in both economic and social equity, while peripheral areas exacerbate socio-economic inequalities. Through spatial analysis and the Coupling Coordination Index (CCI), the study identifies factors influencing the synergy between economic vitality and social equity, such as the density of commercial, sports, and entertainment facilities. The findings emphasize the need for more equitable TOD planning, suggesting that future urban developments should prioritize social inclusiveness alongside economic efficiency. This research expands the theoretical foundation of TOD and offers practical insights for urban planners aiming to achieve sustainable and inclusive urban development.